2019 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--32679
|View full text |Cite
|
Sign up to set email alerts
|

Does Peer Mentoring Help Students be Successful in an Introductory Engineering Course?

Abstract: Previous literature shows that first year engineering students face challenges transitioning from high school to college due to higher academic expectations. In addition to the registration process, financial aid application and tuition requirements, there are other aspects of college admission that add to the challenges for students. For engineering students, the academic challenges arise due to lack of technical and problem-solving skills that are required for higher level mathematics, science and introducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In regards to retention, Gattis et al (2007) showed that peer mentoring led to a 16% increase in retention between the first two semesters for first year engineering students (94% versus 78% for mentored and nonmentored students respectively) [21]. In a different study, peer mentoring in a fundamentals of engineering course was correlated to a 10% increase in students who received a grade of C or higher in the course [22]. Thus, the reviewed literature suggests that there are advantages to the use of peer mentorship in first year engineering classrooms.…”
Section: Literature Reviewmentioning
confidence: 98%
“…In regards to retention, Gattis et al (2007) showed that peer mentoring led to a 16% increase in retention between the first two semesters for first year engineering students (94% versus 78% for mentored and nonmentored students respectively) [21]. In a different study, peer mentoring in a fundamentals of engineering course was correlated to a 10% increase in students who received a grade of C or higher in the course [22]. Thus, the reviewed literature suggests that there are advantages to the use of peer mentorship in first year engineering classrooms.…”
Section: Literature Reviewmentioning
confidence: 98%
“…Within this atmosphere of enrollment pressures and promotion of student success, previous work was carried out at Anderson University, a small enrollment-driven institution, to develop a peer mentorship program for first-year engineering students [2]. This work adapted lessons learned from other, much larger engineering programs into a cohesive peer mentorship program in this smaller context [11,12,13,14,15]. The results of this previous work indicated promising results in short-term retention and an increased feeling of connection with the engineering program.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Tahmina explored the impact of peer mentorship on student success in an introductory engineering course at The Ohio State University at Marion [7]. In their work, they explore two peer mentorship options (a) scheduled peer mentoring, where peer mentors essentially hold open office hours and (b) a mentor-mentee pairing.…”
Section: Introductionmentioning
confidence: 99%